2009
DOI: 10.1177/156482650903000210
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Stability and Sensory Quality of Fermented Fish and Fish Sauce Produced with the Use of Iodated Salt

Abstract: Background. Universal salt iodization promotes the use of iodated salt for producing industrial food products, although it might affect product quality and iodine stability.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…some countries prohibit the addition of iodized salt to processed foods), thereby impacting on food exports. Thus, other components in the diet have been fortified either by including iodized salt as an ingredient, for example with bread (Table 1), or feeding animals iodine-enriched feeds which increase the iodine content of foods produced by these animals, for example in eggs [7], or by the direct addition of an iodine compound to sugar [8], fish sauce [9] and water [10]. The International Council for the Control of Iodine Deficiency Disorders (ICCIDD) does not support the iodization of individual foods.…”
Section: What: Universal Salt Iodization or Fortification Of Individumentioning
confidence: 99%
“…some countries prohibit the addition of iodized salt to processed foods), thereby impacting on food exports. Thus, other components in the diet have been fortified either by including iodized salt as an ingredient, for example with bread (Table 1), or feeding animals iodine-enriched feeds which increase the iodine content of foods produced by these animals, for example in eggs [7], or by the direct addition of an iodine compound to sugar [8], fish sauce [9] and water [10]. The International Council for the Control of Iodine Deficiency Disorders (ICCIDD) does not support the iodization of individual foods.…”
Section: What: Universal Salt Iodization or Fortification Of Individumentioning
confidence: 99%
“…Most studies on the stability of iodine have focused either on iodised salt itself or on the replacement of noniodised salt with iodised salt in various foods (Chanthilath et al ., ), while in the present study, we added various fortificants directly to food vehicles. Therefore, prior data on iodine retention after production of fortified food are relatively limited.…”
Section: Resultsmentioning
confidence: 99%
“…Salt iodisation is a well‐known efficient strategy for combating IDD (Chanthilath et al ., ), and there have been attempts to fortify salt with other micronutrients such as vitamin A, Fe, Zn, calcium and folic acid (Lotfi et al ., ). However, it is technically challenging to fortify salt or other foods with highly bioavailable Fe compounds and iodine, as iodine is unstable and has undesirable organoleptic properties (Diosady et al ., ; Chavasit et al ., ; Wegmüller et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Harrison and Cunningham (1986) found no effect on the viscosity, color or spread of mayonnaise that was prepared with iodized salt; unfortunately, the author did not report the fortificant or concentration of the iodine in the salt. Two studies on use of iodized salt in fish sauce and soy sauce (CNSIC 2004a, b, c;Chanthilath et al 2009) found no significant differences in sauces made with iodized and non-iodized salt. In both, general acceptability was slightly higher for sauce made with iodized salt.…”
Section: Condimentsmentioning
confidence: 99%